PENGARUH PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE YANG DIPADUKAN DENGAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHERHERE (ETH) TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI MIPA SMA NEGERI 1 MUARO JAMBI - Armalina; journal journal (STIT Muhammadiyah Paciran Lamongan, 2019)
Abstract: This study aims to analyze the influences of picture andpicture’smodel implementation that integrated with the learningstrategic active type of everyone is a teacher here (ETH) onstudents’ learning result o biology for students at XI class MIPASMA NEegeri 1 Muaro Jambi. This study employed experimentresearch by using the posttest-only control design. The data consistof quantitative and qualitative data.The result of study shows thatthe integrated of picture and picture learning model and activelearning the everyone is a teacher here (ETH) have an influenceonbiology leraning result for students calss XI MIPA SMA Negeri 1Muaro Jambi cognitive area thas is thitung =4,55 and ttabel=1,671.